2020
DOI: 10.1371/journal.pone.0227948
|View full text |Cite
|
Sign up to set email alerts
|

Some animals are more equal than others: Validation of a new scale to measure how attitudes to animals depend on species and human purpose of use

Abstract: Globally, many millions of animals are used by humans every year and much of this usage causes public concern. A new scale, devised to measure attitudes to animal use in relation to the purpose of use and species, the Animal Purpose Questionnaire (APQ), was completed by in total 483 participants, 415 British nationals and 68 participants from 39 other countries. The APQ was presented in two survey formats, alongside an established Animal Attitudes Scale (AAS). In both surveys, participants also provided demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 46 publications
8
37
2
1
Order By: Relevance
“…Based on the standardized trauma and standardized resuscitation the effect should be investigated on an epigenetic level, since it might be based on an individual reaction to the injury. One might argue that the translation of our results to routine clinical practice might be lacking, however, large animals mirror human physiology better when compared with rodents ( 35 ). For those reasons, a certain translation of our results might be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the standardized trauma and standardized resuscitation the effect should be investigated on an epigenetic level, since it might be based on an individual reaction to the injury. One might argue that the translation of our results to routine clinical practice might be lacking, however, large animals mirror human physiology better when compared with rodents ( 35 ). For those reasons, a certain translation of our results might be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroscience, as it seems, doesn't discriminate on the basis of colour as it is focused on the brain, though it is a different story that whose brain it is studying. There was case when racial discrimination was observed to be processed unintentionally in the brain, while social decision making and attitude formation, between black and white social categories (see Bradley et al, 2020) and how unintentionally race attitude affects legal decision making (see Kubota, Banaji & Phelps, 2012;Matten, Wei, Cloutier & Kubota, 2018). Neuroscience doesn't talk about mysteries of the brain but it reveals something which was unknown earlier and correlates with the intention and behaviour.…”
Section: Decolonizing Brain: Critically Conscious Brain and Lawmentioning
confidence: 99%
“…using an 11 points Likert-type scale ranging from 0 (not worried at all) to 10 (completely worried). Several studies highlighted the importance of analyzing the attitude towards AW depending on the animal species involved (Bradley, Mennie, Bibby, & Cassaday, 2020). Some studies showed that there is a significant positive relationship between knowledge about specific animal species and responsible environmental' attitudes (Bjerke et al 2001;Randler et al, 2005).…”
Section: Students' Concerns Regarding the Welfare Of Farmed Animals' ...mentioning
confidence: 99%